2021
DOI: 10.1002/cnma.202100045
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light Driven CO2 Reduction to Formate with Electron Mediated Nicotinamide‐Modified Viologen in the System of Water‐Soluble Zinc Porphyrin and Formate Dehydrogenase

Abstract: Visible‐light driven CO2 reduction to formate with the system consisting of water‐soluble zinc tetraphneylporphyrin tetrasulfonate (ZnTPPS), formate dehydrogenase from Candida boidinii (CbFDH) and 1‐nicotinamidethy‐1’‐methyl‐4,4’‐ bipyridinium salt (NEMBP) in the presence of triethanolamine (TEOA) as an electron donor was investigated. NEMBP was prepared as the 4,4’‐BP with the nicotinamide‐group to promote the improvement of affinity with CbFDH. The properties of NEMBP were characterized by photochemical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…46c) and was applied as electron carrier. 220,221 The nicotinamide group was introduced in an effort to enhance the affinity of NEMBP with FDH, since the nicotinamide group is present in the structure of the natural occurring NAD + co-enzyme. However, the NEMBP derivative presented disappointing results in all kinetic parameters for CO 2 to formic acid reduction, most likely due to the unfavorable SOMO energy level.…”
Section: Homogeneous Systemsmentioning
confidence: 99%
“…46c) and was applied as electron carrier. 220,221 The nicotinamide group was introduced in an effort to enhance the affinity of NEMBP with FDH, since the nicotinamide group is present in the structure of the natural occurring NAD + co-enzyme. However, the NEMBP derivative presented disappointing results in all kinetic parameters for CO 2 to formic acid reduction, most likely due to the unfavorable SOMO energy level.…”
Section: Homogeneous Systemsmentioning
confidence: 99%
“…7,[13][14][15] In particular, many studies have reported hybrid systems of formate dehydrogenase (FDH), which catalyzes the reduction of CO 2 to formate in the presence of NADH and photoredox systems. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] On the other hand, visiblelight driven CO 2 xation to organic molecules has also garnered much attention in the research eld of green chemistry. [7][8][9][10][11][12] For example, CO 2 as a feedstock is bound to an organic molecule as a carboxy-group based on building C-C bonds to produce a carboxylate.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Unfortunately, NAD + promotes the inverse formate oxidation as well since NAD + has an overwhelmingly higher affinity to enzymes compared with NADH. Recently, more cost-effective articial cofactors such as methyl viologen (MV 2+ ) [17][18][19] were developed, which exhibited even higher conversion rates of CO 2 . However, electron transfer by cofactor diffusion still stems from the photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%